Interfaces Between Intelectual Property, Traditional Knowledge, Genetic Resources And Folklore: Problems And Solutions - Kadirgamar, Hon. Lakshman (Journal of Malaysian and Comparative Law, 2002)
Allow me to begin this lecture with a personal reminiscence. The month of October 1954 is vividly etched in my memory. It was in that month that I, a penniless student, while awaiting the results of the Final Examination for the Admission of Advocates to the Ceylon Bar, came to Malaysia for the first time to spead a holiday with an uncle an eminent lawyer, who lived in Kuala Lumpur.